Water Science & Technology - Water Science & Technology (IWA Publishing, 2026)
Water Science and Technology is IWA Publishing’s flagship Open Access journal with a long history in publishing high-quality peer reviewed papers on all aspects of science and technology related to the wastewater cycle. With a readership across academia and industry, the journal provides a valuable resource for those interested in scientific advances as well as the practical applications of research.
FI 0.43
Q3
Keywords: Physical Sciences & Engineering; Water Resources; Acuerdos transformativos; Transformative agreements; Agua y recursos hídricos; Tratamiento de aguas; Contaminación y procesos químicos; Gestión y sostenibilidad del agua